Educational governance in Africa : a socio-anthropology of public partnership action in education in Cameroon - (:unkn) unknown (My University, 2021)
The purpose of this thesis is the study of partnership governance in public action in education in Cameroon. It was initially inspired by several fundamental questions on the socio-cultural, economic and political situation of this country : how to understand the considerable gap observed in Cameroon between the importance of the investments made by almost all of its national and international actors and partners education and the extreme precariousness in which most of the population lives, as well as the unemployment which affects so many young graduates? Is it not necessary to review the issue of the match between training offers and the job market in this country? In other words, do the education policies implemented in Cameroon embrace the socio-cultural, economic and political realities of this country? These questions have led us to question the modes of governance of education in this country, and more particularly the place and role (possibly) accorded to the actors and partners of this governance.To do this, we carried out a long-term ethnographic survey based on three main sources of information. A documentary research which first revealed a certain weakness in the scientific work of great notoriety on public policies in general in Cameroon and in the field of education in particular. To compensate for this lack of work on which we could have based our analyzes, but also in the absence of reliable written sources and in large number in a country where oral communication still plays a central role in administrative practices, we conducted 56 semi-structured interviews with education policy actors in Cameroon and conducted numerous participant observations in the Cameroonian educational environment.On the theoretical level, our work falls within the current of the socio-anthropology of public action, the relevance of which, in the grasp of the influences of anthropology and sociology on the current issues of public action in general, all
Keywords: African Research